Cybersecurity in Healthcare: How Regulation Is the Key to Pushing Cyber Resilience - Joseph, Jason (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
The digitization of healthcare systems has transformed global healthcare delivery, improving accessibility, diagnostics, and real-time treatment. However, these digital advancements come with significant cybersecurity risks. From legacy HIS systems and cloud-based infrastructure to wearable IoMT and AI-powered diagnostics, every digital touchpoint introduces a potential attack surface. Cyberattacks targeting healthcare can have devastating consequences, ranging from loss of sensitive personal and genomic data to disruption of emergency medical services and national security risks. This review examines how regulation plays a pivotal role in mitigating such risks by enforcing cyber resilience. Drawing from Indian and international case studies, this paper argues that only through a robust, enforceable, and forward-looking regulatory framework—one that includes cyber-bio convergence, threat-sharing mechanisms, and post-quantum preparedness—can healthcare systems evolve into digitally secure ecosystems that protect both patients and infrastructure.